(untitled) (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The aerolysin (aerA) is a virulence indicator used to identify the pathogenicity of the Aeromonas strain. Targeting a pathogen’s crucial virulence gene for detection is essential, as it determines the potential threat to the host. This study aimed to develop a gold nanoparticle (AuNP) probe for detecting the gene aerA in Aeromonas hydrophila among field samples. Materials and Methods: Kidney samples among both healthy and sick Nile tilapias in five provinces of Luzon Island were collected for bacterial analysis. Screening using specific primers targeting aerA was conducted in parallel with testing the AuNPs probe on the same sample set. The positive control provided by BFAR-NFLD, confirmed by polymerase chain reaction (PCR) assay, was used as a positive sample containing the target gene. Results: The AuNP probe demonstrated a computed accuracy of 81.32%, sensitivity of 100%, and specificity of 81.26%. Among the 257 reactions, 59 were false positives, while no false negative results were observed. The AuNP probe could detect aerA at levels as low as 30 ng/µl. The low prevalence of the target gene may be attributed to the use of general media instead of specific media like Rimler-Shotts agar. Conclusion: The established colorimetric detection method for A. hydrophila with the aerA gene offers a swift alternative to PCR, negating the requirement for advanced equipment like a thermal cycler. J. Adv. Vet. Anim. Res., 10(4): 593–598, December 2023 http://doi.org/10.5455/javar.2023.j714